2008
DOI: 10.1007/s12018-008-9023-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone Disease and Idiopathic Hypercalciuria

Abstract: There is sufficient epidemiological and clinical data demonstrating an association between reduced bone mineral density and idiopathic hypercalciuria (IH). There have been relatively few studies that have addressed the underlying defect in bone remodeling. The limited studies to date suggest that increased bone turnover occurs in some forms of IH such as fasting hypercalciuria or renal calcium leak and explains the bone loss observed in these forms of IH. On the other hand, defective bone formation is the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 100 publications
0
10
0
1
Order By: Relevance
“…The fact that these patients are relatively young emphasizes the importance of adequate predictive tools allowing early medical care in this population. Literature is conflicting about the efficiency of biologic markers of bone remodeling in renal-stone formers (5). Here, we studied osteocalcin, bone alkaline phosphatase, and urinary deoxypyridinoline, two markers of bone anabolism and one involved in bone catabolism, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that these patients are relatively young emphasizes the importance of adequate predictive tools allowing early medical care in this population. Literature is conflicting about the efficiency of biologic markers of bone remodeling in renal-stone formers (5). Here, we studied osteocalcin, bone alkaline phosphatase, and urinary deoxypyridinoline, two markers of bone anabolism and one involved in bone catabolism, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the early recognition of patients at risk for osteopenia, before the occurrence of pathologic bone fractures, would be of clinical value. Indeed, because fractures occur after decades, most of observational and epidemiologic works are based upon bone mineral density (BMD) as a surrogate marker in renal-stone formers (4,5). However, BMD measurement in renal-stone formers is expensive and is currently not performed in routine practice, because urolithiasis affects more than 10% of the population in France and most Western countries (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The excretion of urine with an inappropriately high amount of Ca 2ϩ is referred to as hypercalciuria. This condition contributes to the development of osteoporosis and nephrolithiasis (49,52), diseases of Ca 2ϩ mishandling that have significant morbidity and socioeconomic impact.…”
Section: Camentioning
confidence: 99%
“…It has been shown that the incidence of calcium renal lithiasis is higher in patients with losses of bone mineral density, while calciuria levels are also found to be high. 44 Some patients present genetic predisposition towards both calcium renal lithiasis and loss of bone mineral density. 45 Higher incidence of pathological fractures is also seen in osteoporosis patients with calcium renal lithiasis.…”
Section: Loss Of Bone Mineral Density and Calcium Lithiasismentioning
confidence: 99%